Implemetasi Konsep Adiwiyata dalam Pembelajaran Fisika SMAN 10 Bulukumba - Hasan, A. Eka Fitrianti; Suarti, Suarti; Hasanah, Ummul (Al-Khazini, 2021)
The Adiwiyata program is a program prepared by the government in the world of education and creates responsible school citizens in environmental management efforts. SMA Negeri 10 Bulukumba is a school that has implemented the Adiwiyata program. The objectives of this study are: 1) To determine the implementation of curriculum policies related to the concept of adiwiyata in physical learning 2) To determine the implementation of teachers in the integrated physics learning process the concept of adiwiyata. 3)To find out the behavior of students in learning physics with the integration of the concept of adiwiyat. This research is a descriptive qualitative research with ethnographic method. Collecting data using interviews, observation documentation, triangulation. The data analysis technique used in this study was done by analyzing domain and taxonomy results showed that the Adiwiyata curriculum policy in physics learning refers to educational programs, such as graduation competency standards, content standards, process standards, educators and education personnel standards, facilities and infrastructure standards, management standards, education financing standards, educational assessment standards. The implementation of physics subjects with environmentalinsight is integrated into physics subjects through learning activities in the classroomis seen by solving environmental problems using the concept of physicsand outside the classroom is carried out by utilizing the school environment as a physics learning laboratory. But not all physical materials can be integrated with the environment but only certain materials. Student behavior in Adiwiyata learning is seen from student learning to have an attitude of caring for the environment and changing student habits by instilling character values to protect the surrounding environment.